Investigating the stability of fine-grain digit somatotopy in individual human participants - Kolasinski, J; Makin, T; Jbabdi, S; Clare, S; Stagg, C; Johansen-Berg, H (Society for Neuroscience, 2016)
Studies of human somatosensory cortex have placed a strong emphasis on the cortical representation of the hand and the propensity for plasticity therein. Despite many reports of group differences and experience-dependent changes in cortical digit somatotopy, relatively little work has considered the variability of these maps across individuals, and to what extent this detailed functional architecture is dynamic over time. With the advent of 7-tesla fMRI, it is increasingly feasible to map such detailed organisation non-invasively in individual human participants. Here we extend the ability of ultra-high field imaging beyond a technological proof of principle to investigate the inter-subject variability of digit somatotopy across participants, and the stability of this organisation across a range of intervals. Using a well-validated phase-encoding paradigm and an active task, we demonstrate the presence of highly reproducible maps of individual digits in SI, sharply contrasted by a striking degree of inter-subject variability in the shape, extent and relative position of individual digit representations. Our results demonstrate the presence of very stable fine-grain somatotopy of the digits in human SI, and raise the issue of population variability in such detailed functional architecture of the human brain. These findings have implications for the study of detailed sensorimotor plasticity in the context of both learning and pathological dysfunction. The simple task and 10-minute scan required to derive these maps also raises the potential for this paradigm as a tool in the clinical setting.